Pengaruh Pemberian Biosaka dan Vermikompos Terhadap Pertumbuhan dan Hasil Tanaman Cabai Rawit (Capsicum Frutescens L) - Marta Pili; Sunar Wahid; Muhammad Husni (Fakultas Pertanian Universitas Borobudur, 2024)
This study aims to determine the effect of giving biosaka and vermicompost on the growth and yield of cayenne pepper plants (Capsicum frutescens L). This research was conducted at the Experimental Garden of the Faculty of Agriculture, Borobudur University, East Jakarta from June to November 2023. This study used a Factorial Randomized Group Design, with two factors, namely: factor of biosaka 0 ml, biosaka 2 ml, biosaka 4 ml, and factor of vermicompost 0 grams, vermicompost 25 grams, vermicompost 50 grams, vermicompost 75 grams. This study measured 5 parameters: plant height, stem diameter, number of fruits, fruit weight, and root length. Analysis of variance (ANOVA) data showed that the interaction effect of giving biosaka and vermicompost on the growth and production of cayenne pepper plants showed a real difference (Significant) at the age of 2 weeks after planting. However, it was insignificant at the age of 4 weeks, 6 weeks, 8 weeks, 10 weeks, 12 weeks, and 14 weeks. It is suspected that plants still have sufficient food reserves at the beginning of the planting period. This food reserve is contained in the endosperm, and gets additional nutrients from the soil that has been mixed with vermicompost as a nutrient enhancer.